Vivências anímicas e percepção subjetiva de qualidade de vida: perspectiva de servidores públicos nos âmbitos da saúde e da educação - Pacheco, José Pedro Scarpel [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study was qualitative in nature and aimed to investigate the possible interference of spiritual experiences with the subjective perception of quality of life. The perspectives of civil servants in education and health services were compared. The study was developed through bibliographic and exploratory research, and the instrument used for data collection for the exploratory research was the WHOQOL-bref, which was applied in two stages: before and after experiences with spiritual activities. The purposive sample used in this study was composed of civil servants working in health and education administrative sectors of the Brazilian Unified Health System and a State University, respectively, with the intention of broadening the understanding about the perception of quality of life in civil servants from different sectors. The exploratory research of the study was carried out in three stages. The first was a two-phase data collection, before and after experiences with spiritual activities offered to civil servants who worked in the health care field, as well as the analysis of the results of this step. The second stage was the collection of data before and after experiences with spiritual activities offered to civil servants who worked in the administrative sector of education in a public university, besides the analysis of the results of this step. The third stage consisted of a comparison of the results obtained in the preceding two steps. The data resulting from the use of the research instrument for both samples were analyzed via Thematic Content Analysis. A questionnaire containing 26 questions based on four main themes was used. The first two questions were related to perceived quality of life and health satisfaction and they were not part of the specific domains. The other 24 questions were divided between the four themes: physical domain, psychological domain, domain of social relations, and environmental domain. The results...

Este estudo, de natureza qualitativa, teve como objetivo investigar as possíveis interferências de vivências anímicas na percepção subjetiva de Qualidade de Vida, comparando-se as perspectivas de Servidores Públicos, dos âmbitos da Saúde e da Educação. O estudo foi desenvolvido por meio de pesquisas bibliográfica e exploratória, utilizando como instrumento para a coleta de dados da pesquisa exploratória o WHOQOL-bref, aplicado, de modo bifásico, antes e após vivências com atividades anímicas. A amostra intencional do estudo foi composta por Servidores Públicos, atuantes nos setores administrativos da Saúde e da Educação, respectivamente, do Sistema Único de Saúde e de uma Universidade Estadual, com a intenção de ampliar a compreensão sobre a percepção de Qualidade de Vida para Servidores Públicos de diferentes segmentos. A pesquisa exploratória do estudo foi desenvolvida em três etapas, em que a primeira foi relativa a uma coleta bífásica de dados, sendo pré e pósvivências com atividades anímicas, oferecidas aos Servidores Públicos que atuam no âmbito da Saúde, assim como, a análise dos resultados desta etapa. A segunda etapa foi referente à coleta de dados pré e pós- vivências com atividades anímicas, oferecidas aos Servidores Públicos que atuam no setor administrativo da Educação, em uma Universidade Pública, assim como, a análise dos resultados desta etapa. A terceira etapa foi relativa a um estudo comparativo dos resultados obtidos nas duas etapas anteriores. Os dados resultantes da aplicação do instrumento para as duas amostras participantes do estudo foram analisados com base na técnica de Análise de Conteúdo Temático. Foram estabelecidos 4 eixos temáticos, em um questionário composto por 26 questões, sendo que as duas primeiras questões são referentes a percepção de Qualidade de Vida e satisfação com a saúde, não fazendo propriamente parte dos domínios específicos...
Keywords: Educação fisica; Qualidade de vida; Saúde do trabalhador; Servidores públicos